Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1472-6963-12-459
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of advanced liver disease among patients with Hepatitis C Virus: a large state Medicaid perspective

Abstract: BackgroundChronic hepatitis C virus (HCV) may progress to advanced liver disease (ALD), including decompensated cirrhosis and/or hepatocellular carcinoma (HCC). ALD can lead to significant clinical and economic consequences, including liver transplantation. This study evaluated the health care costs associated with ALD among HCV infected patients in a Medicaid population.MethodsUsing Florida Medicaid claims data, cases were patients with at least 1 diagnosis of HCV or prescription therapy for HCV (ribavirin pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 15 publications
(27 reference statements)
2
27
0
2
Order By: Relevance
“…The three factors that had the highest contribution to total cost for in‐patients were the presence of ESRD, presence of HCV and higher mean Charlson score; the three factors that had the highest contribution to total cost for out‐patients were the presence of ESRD, high mean Charlson score and being disabled. Our findings are consistent with prior studies . Also, Galbraith et al .…”
Section: Discussionsupporting
confidence: 94%
“…The three factors that had the highest contribution to total cost for in‐patients were the presence of ESRD, presence of HCV and higher mean Charlson score; the three factors that had the highest contribution to total cost for out‐patients were the presence of ESRD, high mean Charlson score and being disabled. Our findings are consistent with prior studies . Also, Galbraith et al .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that, as a potential cost‐saving measure under Medicare‐managed care, patients were discharged sooner and, if unable to go home with or without assisted help, were discharged to a care facility for further treatment. This was especially true for HCV patients categorized into the extreme illness category who were almost six times more likely to be discharged to an intermediate care facility and approximately three times more likely to be discharged to home with home health care . These data may help explain the contradictory finding of higher charges but no increase in hospital costs or in a patient's length of stay.…”
Section: Discussionmentioning
confidence: 92%
“…The economic impact of HCV‐related healthcare costs has been studied by both Menzin and colleagues and Gordon with his co‐investigators . They found healthcare costs increased with the severity of illness and was the highest for those with end‐stage liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis C virus (HCV) is estimated to affect more than 3 million Americans and is characterized by both hepatic and extrahepatic manifestations that can impact patients' lives . In terms of direct economic burden, substantial costs are historically associated with advanced disease and inpatient care . Recent innovations in drug therapy provide the opportunity for clinical cure of this chronic infection.…”
Section: Introductionmentioning
confidence: 99%